Martial Arts “Kendo” and the Motivation Network During Attention Processing: An fMRI Study - Fujiwara, Hironobu; Ueno, Tsukasa; Yoshimura, Sayaka; Kobayashi, Kei; Miyagi, Takashi; Oishi, Naoya; Murai, Toshiya (Frontiers in Human Neuroscience, 2019)
Japanese martial arts, Budo, have been reported to improve cognitive function, especially attention. However, the underlying neural mechanisms of the effect of Budo on attention processing has not yet been investigated. Kendo, a type of fencing using bamboo swords, is one of the most popular forms of Budo worldwide. We investigated the difference in functional connectivity (FC) between Kendo players (KPs) and non-Kendo players (NKPs) during an attention-related auditory oddball paradigm and during rest. The analyses focused on the brain network related to “motivation”. Resting-state functional magnetic resonance imaging (fMRI) and task-based fMRI using the oddball paradigm were performed in healthy male volunteers (14 KPs and 11 NKPs). Group differences in FC were tested using CONN-software within the motivation network, which consisted of 22 brain regions defined by a previous response-conflict task-based fMRI study with a reward cue. Daily general physical activities were assessed using the International Physical Activity Questionnaire (IPAQ). We also investigated the impact of major confounders, namely, smoking habits, alcohol consumption, IPAQ score, body mass index, and reaction time (RT) in the oddball paradigm. Resting-state fMRI revealed that KPs had a significantly lower FC than NKPs between the right nucleus accumbens and right frontal eye field within the motivation network. Conversely, KPs exhibited a significantly higher FC than NKPs between the left intraparietal sulcus and the left precentral gyrus within the network during the auditory oddball paradigm (statistical thresholds, FDR < 0.05). These results remained significant after controlling for major covariates. Our results suggest that attenuated motivation network integrity at rest together with enhanced motivation network integrity during attentional demands might underlie the instantaneous concentration abilities of KPs.